Dynamics of Megaelectron Volt Electrons Observed in the Inner Belt by PROBA‐V/EPT. Issue 3 (18th March 2019) - Pierrard, V.; Lopez Rosson, G.; Botek, E.
Abstract: Using the observations of the EPT (Energetic Particle Telescope) onboard the satellite PROBA‐V, we study the dynamics of inner and outer belt electrons from 500 keV to 8 MeV during quiet periods and geomagnetic storms. This high time‐resolution (2‐s) spectrometer operating at the altitude of 820 km on a low polar orbit is providing continuously valuable electrons fluxes for already 5 years. We emphasize especially that some megaeleactron volt electrons are observed in low quantities in the inner belt, even during periods when they are not observed by Van Allen Probes. We show that they are not due to proton contamination but to clear injections of particles from the outer belt during strong geomagnetic storms of March and June 2015, and September 2017. Electrons with lower energy are injected also during less strong storms and the L shell of the electron flux peak in the outer belt shifts inward with a high dependence on the electron energy. With the new high‐resolution EPT instrument, we can study the dynamics of relativistic electrons, including megaelectron volt electrons in the inner radiation belt, revealing how and when such electrons are injected into the inner belt and how long they reside there before being scattered into the Earth's atmosphere or lost by other mechanisms. Plain Language Summary: New high resolution EPT/PROBA‐V measurements of the electrons fluxes allow us to better understand the dynamics of the electrons in the inner and outer radiation belts. EPT put in perspective the VAP discovery that the expected population of MeV electrons in the inner belt was "missing" and that previous studies suggesting a long‐lived, relatively static inner radiation belts likely misidentified penetrating protons as inner belt electrons. Some MeV electrons are observed by EPT in the inner belt, but in very low quantity. This observation of EPT cannot be due to proton contamination since injections associated to geomagnetic storms are clearly identified. The new capability of EPT to well discriminate the particle species and energy ranges led to new discoveries concerning their source and loss mechanisms regarding the dynamics in this region. Key Points: Five years of EPT observations show injections of energetic electrons in the slot region and in the inner belt during strong geomagnetic storms EPT detects megaelectron volt electrons present in the inner belt, especially in the south part of the South Atlantic Anomaly (SAA) The penetration of the electrons in the SAA is strongly dependent on the geomagnetic activity level and on the energy of the electrons